Rogue sun (2022), volume 4 ebook - Parrott, Ryan (Rogue Sun (2022), 2025)
The fourth volume in a supernatural murder mystery that explores the complicated bond between father and son and cements itself squarely in a corner of the MASSIVE-VERSE! Finally back in control of his life, Dylan attempts to repair the damage inflicted on New Orleans in his absence while preparing himself for the ultimate showdown with Mourningstar. But as he begins scouring the supernatural community for allies, he discovers new players lurking in the shadows, each with their own agendas—and not everyone wants him to succeed. Collects ROGUE SUN #19-24